COMPARATIVE ANALYSIS OF THE PROPERTIES OF NANORELIEF VARIOUS GOLD-BEARING SULPHIDES - A E Vorob’ev; Honore Tcharo (RUDN Journal of Engineering Research, 2016)
The results of a comparative analysis of the different properties of nanorelief gold sulfides are presented. The morphology and microtopography of auriferous pyrite and arsenopyrite are described. The mechanism of adsorption of gold on the surface of sulphides, which is based on redox reactions isexplained. It is shown that gold is adsorbed largely on arsenopyrite surface than on pyrite surface. The mechanism of adsorption of gold sulfide by surface defects is explained.